Understanding Blackness in South Korea: Experiences of one Black Teacher and one Black Student (Global Journal of Human-Social Science, 2017)
This study examines the experiences of one Black individual (Wilkine Brutus) who worked as a teacher and one Black individual (Sam Okyere) who was a university student in South Korea. The purpose of this study was to understand the meaning of Blackness in South Korea and how it is constructed, how anti-Black sentiments affect Black individuals, and how Black individuals -given the opportunity in South Korea in diverse fields -may shape and transform the construct of Blackness in the country. This study raises a number of issues in the Korean context where Black individuals are being discriminated against because of their race and skin color, and are denied opportunities, especially in the field of education.
Keywords: blackness; race; discrimination; south korea; education; multicultural; black teacher; black student